The effectiveness of galactomyces ferment filtrate, dexpanthenol, and Centella asiatica combination serum in the treatment of post-acne hyperpigmentation - We Sagara Dewi; Ivan Kurniadi; Anis Irawan Anwar (Explorer Front, 2020)
Background: Acne vulgaris is a chronic inflammation of the pilosebaceous gland that may result in non-inflammatory and inflammatory lesions. A hypermelanotic reaction to skin inflammation causes post-acne hyperpigmentation (PAH). It can occur secondary to the inflammation process and, depending on the severity, may persist for a prolonged period. Objective To determine the effectiveness of galactomyces ferment filtrate (GFF), dexpanthenol, and Centella asiatica combination serum in the treatment of PAH Methods: This was a placebo-controlled randomized clinical trial. Sixty-eight subjects were divided into two groups: the experimental group received combination serum while the control group received a placebo for eight weeks. Three drops of serum were applied to the area with PAH twice daily in the morning and night. The melanin, erythema, roughness, and L*, a*, and b* scores were assessed objectively using mexameter, chromameter and skin analyzer every two weeks. Pearson’s correlation test and independent T-test were used to assess the trend of the parameters and compare the results of both groups. Results: The results of statistical calculations using the Pearson correlation test showed the treatment group showed a significant decreasing trend of the melanin and spots score. Both groups showed a significant decreasing trend in erythema, L* score and roughness. However, no significant difference was found between both groups in all parameters. Conclusion: The combination serum may decrease the melanin and spot scores suggesting that it affects the melanocyte activity. It has shown good efficacy in treating PAH.